Determinants of tax administration efficiency in Libya - Muaen, Moftah A. O. (2016)
Tax is one major source of government revenue, however, not every national government has been able to effectively exploit this great opportunity of revenue generation. The tax is collected at very lower level because of the inefficiency of tax administration in Libya. The purpose of this study is to investigate the determinants of tax administration efficiency from the Libyan perspective. This study is based on five variables that are used to determine the factors that affect tax administration efficiency in Libya. The five variables that are measured in this current study are autonomy, motivation, information and communication technology ICT, training and leadership style. The data were collected through the distribution of questionnaires to 250 respondents in Libya. 161 out of 250 questionnaires were sufficient and a valid rate for the analysis by using the Partial Lease Square-Structural Equation Modeling (PLS-SEM) software. By using correlation and regression analyses, the outcomes of the study show that there is a positively and significant relationship between motivation, ICT training and leadership style with tax administration efficiency. On the other hand, autonomy indicates a negative and insignificant relationship with tax administration efficiency.